Borobudur cultural landscape : a madilog discourse - I Gede, Wiwin Suyasa; Astawa , I Putu; Soeroso , Amiluhur (International Journal of Applied Sciences in Tourism and Events, 2023)
Borobudur, an ancient monument renowned as a prominent tourist attraction for years, has traditionally been scrutinized through the lens of mystical logic, with prevailing discussions revolving around spiritual influences and supernatural elements. This perspective posits that every aspect of Borobudur, from its construction to its purpose, is intrinsically linked to spiritual motivations. However, a departure from this mystical logic emerges in contemporary research studies that delve into Borobudur's facets through various disciplines such as geography, geology, architecture, and astronomy. This shift aims to explore the cultural landscape of Borobudur during its construction in the eighth century from a different standpoint. In a departure from the mystical approach, this study adopts Tan Malaka's Madilog method to present a fresh perspective on Borobudur's cultural landscape. Through this alternative approach, the study unveils a compelling revelation: Borobudur's cultural landscape development aligns significantly with sustainable and economic sustainability principles. Contrary to the prevailing mystical narratives, Tan Malaka's Madilog sheds light on the pragmatic aspects of Borobudur's construction era, emphasizing a connection to broader concepts of sustainability and economic viability. This nuanced exploration broadens our understanding of Borobudur and highlights the importance of considering diverse methodological approaches to unlock the multifaceted dimension of this historical monument.